The Stadium and the City: Sports infrastructure in late imperial Ethiopia and beyond - Katrin Bromber (Cadernos de Estudos Africanos)
The inauguration of the Haile Selassie I Stadium in Addis Ababa in 1947 marked the beginning of the construction of stadiums in Ethiopia. They became important signifiers of accelerated modernisation after the end of the Italian occupation (1935-1941). Quite similar to developments elsewhere, open fields were turned into formalised sport infrastructures. Already in the 1930s, stadiums had become essential elements of modern town planning in Ethiopia. Later, political officials, town planners and sport enthusiasts endowed them with specific meanings, involving ideas of progress, effective representation of political power and ‘useful’ recreation.